Photobleaching of Arterial Autofluorescence for Immunofluorescence Applications - Karl Kingsley; Kilpatrick Carroll; Janice L. Huff; George E. Plopper (BioTechniques)
Immunohistochemical localization of low-level antigens in the arterial vasculature is complicated by the presence of complex molecules such as collagen, elastin, cholesterol, and fluorescent lipids that exhibit autofluorescence over a wide spectrum of wavelengths. UV irradiation of arterial vasculature has remained ineffective in preparing samples for immunofluorescent staining because of the recovery of the endogenous fluorescence within a short time following treatment. Therefore, we sought to further enhance the signal-to-noise ratio in arteries by optimizing the photobleaching of this tissue. We report here that the use of filtered sunlight significantly reduces arterial autofluorescence compared to standard UV shortwave and longwave irradiation and maintains multiple antigen epitopes suitable for immunohistochemical analysis. Using this method, we localized low-level laminin-5 isoform expression in situ, which was previously indistinguishable from endogenous autofluorescence.